Non-linear dose-response relationship between the visceral adiposity index and diabetes in adults with normoglycemia: a cohort study - Liang, Xiaomin; Xing, Zemao; Li, Ying; Gui, Shuiqing; Hu, Haofei (Frontiers in Endocrinology, 2024)
Objective: Previous studies have identified a positive link with visceral adiposity index (VAI) and diabetes in specific populations. Our investigation focused on examining these associations among normoglycemic adults in Japan.A cohort study of NAGALA (NAfld in the Gifu Area Longitudinal Analysis) was undertaken from 2004 to 2015 in Japan. The link on VAI and diabetes was evaluated using multivariate Cox proportional hazards regression and restricted cubic spline (RCS) regression models.Receiver operating characteristic (ROC) curve analysis was performed to assess the predictive value of VAI for incident diabetes.Results: Our study included 15,452 participants, with 8418 males (54.48%) and 7034 females (45.52%). The average age was 43.71 ± 8.90, and 373 participants (2.41%) developed diabetes. VAI is positively related to diabetes (HR=1.13, 95% CI 1.08-1.18). The inflection point of non-linear relationship was observed at a VAI of 4.67. For VAI values up to 4.67, a unit rise in VAI related to a 24% surge in new-onset diabetes (HR=1.24, 95% CI 1.12-1.37, p<0.0001). Subgroup analysis detected a more robust relation in females (HR=1.40, 95% CI 1.14-1.70, p=0.0010). ROC analysis indicated that VAI with an AUC of 0.7479 (95% CI: 0.7237-0.7720) had better predictive power.Our cohort study validated the positive and non-linear relations for VAI and diabetes among normoglycemic adults in Japan. The relevance was more marked for females than for males.By maintaining VAI below 4.67, a further reduction in VAI could potentially lead to a significant decrease in diabetes risk.